2013
DOI: 10.1016/j.ijsu.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Hip fracture surgery: Does time of the day matter? A case-controlled study

Abstract: Outcomes in terms of adequacy of fixation, post-operative complications and post-operative 30-day mortality are comparable to routine day time surgery while offering the benefits of early fixation and mobilization to the patient. This also has a positive impact on the financial burden on this population as early fixation translates into decreased length of stay and reduced cost of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…Nighttime kidney transplantation is not associated with increased risk of surgical complications, and survival is independent of the operative time of day [14]. In hip fracture surgery, apart of operative time of day, postoperative complications and postoperative 30-day mortality are comparable, and when an appropriate surgical team is on duty, there was no significant difference between postoperative morbidity and mortality [15,16]. Regarding colorectal surgery, it seems that nighttime colorectal surgery is an independent risk factor for anastomotic leakage and patients having nighttime urgent and emergent colorectal surgery were more likely to die [17,18].…”
Section: Introductionmentioning
confidence: 96%
“…Nighttime kidney transplantation is not associated with increased risk of surgical complications, and survival is independent of the operative time of day [14]. In hip fracture surgery, apart of operative time of day, postoperative complications and postoperative 30-day mortality are comparable, and when an appropriate surgical team is on duty, there was no significant difference between postoperative morbidity and mortality [15,16]. Regarding colorectal surgery, it seems that nighttime colorectal surgery is an independent risk factor for anastomotic leakage and patients having nighttime urgent and emergent colorectal surgery were more likely to die [17,18].…”
Section: Introductionmentioning
confidence: 96%
“…Some studies defined complications as medical complications or unplanned return to the operating room, 15,24 whereas others reported only wound infection, urinary tract infection, and deep vein thrombosis. 19 Thus direct comparison with these studies was not possible. Further comparison of blood transfusion rate with previous studies was performed, as it represented the most common complication.…”
Section: Postoperative Complication Ratementioning
confidence: 98%
“…This was supported by a study in 2013 that showed no significant difference in postoperative complication rate or mortality rate after reviewing 220 dynamic hip screw surgeries in terms of their operating time. 19 It concluded that out-of-hours surgery offers the benefit of early fixation and mobilisation, and hence may shorten the length of stay and reduce cost of treatment. 19 Chacko et al 14 also reported similar findings in 171 hip fracture patients with surgical intervention where mortality rate within 1 month and complication rate were comparable between the daytime and night-time groups.…”
Section: Outcomes Of Daytime and Out-of-hours Surgerymentioning
confidence: 99%
See 2 more Smart Citations